Formation of d-wave superconducting order in a randomly doped lattice - Loktev, V.M.; Pogorelov, Yu.G. (Физика низких температур, 2001)
We consider the interplay between superconducting coupling and dopant impurity

scattering of charge carriers in planar square lattice systems and examine the physical

conditions (doping level, temperature, local symmetry of coupling and scattering

potentials) necessary in this model system to obtain a d-wave superconducting order, like

that observed in real doped cuprate HTSC materials. Using the Lifshitz model for the

disorder introduced into system by dopants, we analyze also the nonuniform structure of

such a d-wave parameter, including both its magnitude and phase variation. The results

indicate that d-wave superconductivity becomes possible in a doped metal until it is

destroyed at too high doping levels.